Efektivitas Pemberian Kombinasi Teh Daun Mint (Mentha piperita) dan Madu terhadap Intensitas Nyeri Haid (Dismenore): Effectiveness Giving a Combination of Mint Leaf Tea (Mentha piperita) and Honey Against Menstrual Pain Intensity (Dysmenorrhea) - Nafara Aghnia Anfusufi; Adam M. Ramadhan; Vita Olivia Siregar (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Dysmenorrhea or menstrual pain is still a major problem for most women. There are many ways to deal with menstrual pain or dysmenorrhea, one of which is by consuming herbal drinks. Mint leaves contain menthol compounds which can reduce contractions in the myometrium so that the pain of dysmenorrhea that is felt can be reduced. Flavonoids contained in honey can reduce pain by inhibiting the formation of prostaglandins through inhibition of the cyclooxygenase enzyme. So that the combination of the two can work synergistically in reducing the intensity of dysmenorrhea pain. This study aims to determine the effectiveness of giving mint leaf tea (Mentha piperita) and honey to reduce the intensity of menstrual pain (dysmenorrhea). The research method used was quasy experimental with purposive sampling and obtained 50 respondents divided into 2 groups. The results obtained in the two groups of respondents after giving the combination of mint leaf tea and honey for 2 days were a decrease between the pretest and posttest with a significance value of 0.000 (p